Answer:
f(x) = 10 [ (x + 4)^2 = -6 ]
Explanation:
Please use " ^ " to indicate exponentation. Thanks.
Also, please share the possible answer choices. "Select the best answer from the choices provided."
Start with f(x) = 10x^2 + 80x + 220 = 0
Factor out the 10 to simplify this "completing the square."
f(x) = 10(x^2 + 8x + 22) = 0
Complete the square of x^2 + 8x + 22 only, for now.
Identify the coefficient of the x term. It is 8. Take half of that (it is 4) and square your result: 16
Now add 16 to x^2 + 8x and then subtract 16 from that sum:
x^2 + 8x + 16 - 16 + 22 = 0, or
x^2 + 8x + 16 + 6 = 0
Rewrite x^2 + 8x + 16 as (x + 4)^2
and then the whole expression x^2 + 8x + 16 - 16 + 22 as (x + 4)^2 = -6
Finally, rewrite this as
f(x) = 10 [ (x + 4)^2 = -6 ] which is the desired form of the original equation.